A ratiometric fluorescent system for carboxylesterase detection with AIE dots as FRET donors1. Issue 64 (18th August 2015) - Wu, Yinglong; Huang, Shuailing; Zeng, Fang; Wang, Jun; Yu, Changmin; Huang, Jing; Xie, Huiting; Wu, Shuizhu
<x xml:space="preserve">Abstract</x> A ratiometric fluorescence CaE assay was developed with AIE dots as donors in the FRET process for the first time, which is capable of detecting esterase in human serum.